Proceedings of SPE Annual Technical Conference and Exhibition 1992
DOI: 10.2523/24682-ms
|View full text |Cite
|
Sign up to set email alerts
|

Transient Pressure Response of Horizontal Wells in Layered and Naturally Fractured Reservoirs With Dual-Porosity Behavior

Abstract: Over the last decade, extensive studies have been carried out on the behaviour of vertical well tests in dual porosity systems. Although some research has been done on the horizontal well counterpart [1-51, most of this work has just dealt with a specific situation. No systematic investigation has been yet reported on the behaviour of transient horizontal well tests in dual porosity systems. One of the major purposes of this study is to bridge this gap. An approximate analytic solution in real time space model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Briceño et al (2002), it was reported that a bilinear flow regime is observed in well tests for horizontal wells that are overlying or underlying formations with a shale barrier. This was attributed to the transient double porosity behavior as explained by Du and Stewart (1992) above.…”
Section: Dual Layer Formation With Higher-permeability Layer Overlyinmentioning
confidence: 91%
See 3 more Smart Citations
“…Briceño et al (2002), it was reported that a bilinear flow regime is observed in well tests for horizontal wells that are overlying or underlying formations with a shale barrier. This was attributed to the transient double porosity behavior as explained by Du and Stewart (1992) above.…”
Section: Dual Layer Formation With Higher-permeability Layer Overlyinmentioning
confidence: 91%
“…Unless mentioned otherwise, all the following models are for a horizontal well length, L of 3000ft, an average horizontal permeability, k H of 50mD and a total reservoir thickness, h of 120ft. Du and Stewart (1992) claimed that a transient double-porosity behavior during intermediate-times can lead to a bilinear flow regime. For a horizontal well within a higher-permeability layer overlying a lowerpermeability layer, this is analogous to a dual-porosity system where two regions of different storativity and mobility exist.…”
Section: Base Model Construction and Verificationmentioning
confidence: 98%
See 2 more Smart Citations
“…In the first paper published on this subject, de Carvalho and Rosa (1988) used the pseudosteady-state flow conditions in matrix blocks with the s → s f (s) transformation to derive the pressure transient solution for a horizontal well in a naturally fractured reservoir. After the de Carvalho and Rosa (1988) solution, many more solutions have been published in the petroleum literature using the → s f (s) transformation, while varying the matrix block shape and matrix block flow condition, and adding the interporosity skin factor for the matrix (Aguilera and Ng 1991;Du and Stewart 1992;Williams and Kikani 1990), in addition to the more recent papers by Abdulal et al (2011), Brohi et al (2011), Guo et al (2012, Ketineni and Ertekin (2012), Lu et al (2009), Medeiros et al (2007, 2008, 2010, Nie et al (2012a, b), Torcuk et al (2013).…”
Section: Introductionmentioning
confidence: 99%